1999
DOI: 10.1038/sj.onc.1202239
|View full text |Cite
|
Sign up to set email alerts
|

Dominant effects of the bcr-abl oncogene on Drosophila morphogenesis

Abstract: We targeted expression of human/¯y chimeric Bcr-Abl proteins to the developing central nervous system (CNS) and eye imaginal disc of Drosophila melanogaster. Neural expression of human/¯y chimeric P210 Bcr-Abl or P185 Bcr-Abl rescued abl mutant¯ies from pupal lethality, indicating that P210 and P185 Bcr-Abl can substitute functionally for Drosophila Abl during axonogenesis. However, increased levels of neurally expressed P210 or P185 Bcr-Abl but not Drosophila Abl produced CNS defects and lethality. Expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 65 publications
1
28
0
Order By: Relevance
“…Interestingly, each Bcr-Abl isoform can rescue abl mutants, suggesting that their signaling properties are not grossly altered. However, neural-specific expression of these oncogenes in a wild-type background disrupts CNS development, whereas neural-specific overexpression of wildtype Abl does not, suggesting that regulated kinase activity is important (Fogerty et al, 1999). Interestingly, some neuronal Bcr-Abl phenotypes resembled those of ena loss-offunction, and Ena phosphorylation was increased in Bcr-Abl expressing flies, consistent with Ena being a Bcr-Abl target.…”
Section: Introductionmentioning
confidence: 51%
See 3 more Smart Citations
“…Interestingly, each Bcr-Abl isoform can rescue abl mutants, suggesting that their signaling properties are not grossly altered. However, neural-specific expression of these oncogenes in a wild-type background disrupts CNS development, whereas neural-specific overexpression of wildtype Abl does not, suggesting that regulated kinase activity is important (Fogerty et al, 1999). Interestingly, some neuronal Bcr-Abl phenotypes resembled those of ena loss-offunction, and Ena phosphorylation was increased in Bcr-Abl expressing flies, consistent with Ena being a Bcr-Abl target.…”
Section: Introductionmentioning
confidence: 51%
“…Previous work demonstrated that regulated Abl activity is necessary for the correct development of the CNS and that CNS-specific expression of Bcr-Abl disrupts the CNS and results in embryonic lethality (Fogerty et al, 1999). Therefore, we assessed whether the embryonic lethality we observed using our GAL4 drivers was due to CNS disruption.…”
Section: Expression Of Abl or Bcr-abl Leads To Embryonic Lethality Anmentioning
confidence: 99%
See 2 more Smart Citations
“…All crosses were performed at 25°C unless otherwise indicated. The following strains were obtained from various sources: upstream activation sequence (UAS)-kette Myr /TM6B (6), UAS-dAbl/CyO (14), and UAS-dAbl K417N / CyO (14). To generate the PTP61F-RNA interference (RNAi) construct, the PTP61F DNA (coding sequence ϩ901 to ϩ1415) was cloned as an inverted repeat into the pWIZ vector (28).…”
Section: Methodsmentioning
confidence: 99%